Insecticidal Activities of Bark, Leaf and Seed Extracts of Zanthoxylum heitzii against the African Malaria Vector Anopheles gambiae - Overgaard, Hans J. (Molecules, 2014)
The olon tree, Zanthoxylum heitzii (syn. Fagara heitzii) is commonly found in the central-west African forests. In the Republic of Congo (Congo-Brazzaville) its bark is anecdotally reported to provide human protection against fleas. Here we assess the insecticidal activities of Z. heitzii stem bark, seed and leaf extracts against Anopheles gambiae s.s, the main malaria vector in Africa. Extracts were obtained by Accelerated Solvent Extraction (ASE) using solvents of different polarity and by classical Soxhlet extraction using hexane as solvent. The insecticidal effects of the crude extracts were evaluated using topical applications of insecticides on mosquitoes of a susceptible reference strain (Kisumu [Kis]), a strain homozygous for the L1014F kdr mutation (kdrKis), and a strain homozygous for the G119S Ace1R allele (AcerKis). The insecticidal activities were measured using LD(50) and LD(95) and active extracts were characterized by NMR spectroscopy and HPLC chromatography. Results show that the ASE hexane stem bark extract was the most effective compound against An. gambiae (LD(50) = 102 ng/mg female), but was not as effective as common synthetic insecticides. Overall, there was no significant difference between the responses of the three mosquito strains to Z. heitzii extracts, indicating no cross resistance with conventional pesticides.